2022
DOI: 10.1186/s12888-022-04290-7
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming adult ADHD into primary care in the UK: guidance, practice, and best practice recommendations

Abstract: Background ADHD in adults is a common and debilitating neurodevelopmental mental health condition. Yet, diagnosis, clinical management and monitoring are frequently constrained by scarce resources, low capacity in specialist services and limited awareness or training in both primary and secondary care. As a result, many people with ADHD experience serious barriers in accessing the care they need. Methods Professionals across primary, secondary, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 92 publications
1
37
0
1
Order By: Relevance
“…It has been suggested that some people with ADHD could be diagnosed and managed entirely 38 or partially 39 in primary care. This would be a substantial shift away from the UK's current national guidelines, which state that a diagnosis of ADHD ‘should only be made by a specialist psychiatrist, paediatrician or other appropriately qualified healthcare professional with training and expertise in the diagnosis of ADHD’.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that some people with ADHD could be diagnosed and managed entirely 38 or partially 39 in primary care. This would be a substantial shift away from the UK's current national guidelines, which state that a diagnosis of ADHD ‘should only be made by a specialist psychiatrist, paediatrician or other appropriately qualified healthcare professional with training and expertise in the diagnosis of ADHD’.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, these guidelines state that ADHD should only be diagnosed based on a full clinical and psychosocial assessment, full developmental and psychiatric history and observer reports. 14 Few primary care clinicians currently have the training to do so, or the time (a ‘straightforward’ ADHD assessment may take 2 h, 39 whereas the standard appointment in UK primary care is 10 min long 40 ). Novel solutions could involve a hybrid approach, developing the role of primary care practitioners with special expertise in ADHD in management and perhaps even diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NHS Community Mental Health Framework,24 also sets out a vision for how community services should modernise to offer joined-up-care for those with mental health needs, within ICSs. Recent guidance, stemming from professionals across primary, secondary, and tertiary care in the UK, has recommended the development of an ADHD specialism within primary care, as part of a roadmap for improving access to treatment 25. The evidence base outlined above, and current guidelines,7 highlight the key role primary care services have to play in the provision of healthcare for young people with ADHD, and the potential for supporting an expansion of this role.…”
Section: Introductionmentioning
confidence: 99%
“…Long waiting lists push the dwindling GP workforce to do more work, which is unfunded and unsustainable. The UK Adult ADHD Network has proposed potential solutions to ADHD waiting lists 4…”
mentioning
confidence: 99%